Relationship of nursing services to the level of patient satisfaction: A literature review - Gurning, Maylar; Duwith, Yopi (Science Center Group, 2024)
Background: Patient satisfaction represents an important indicator for evaluating the quality of health services, particularly nursing care delivered in hospital settings. Nurses maintain continuous contact with patients during treatment processes, making nursing services a key determinant of patient experiences and satisfaction outcomes. Objective: This study aimed to analyze the relationship between nursing service quality and the level of patient satisfaction through a literature review. Methods: This study used a literature review design following the PRISMA guideline recommended by the EQUATOR Network. The data were secondary data derived from previously published research articles. The literature search was conducted using Google Scholar with keywords related to patient satisfaction, nursing services, and service quality. The inclusion criteria included full-text research articles published between 2019 and 2024 that examined nursing service quality and patient satisfaction. A total of ten studies met the inclusion criteria and were analyzed using a narrative synthesis approach. Results: The review of five selected studies showed consistent evidence that nursing service quality significantly influences patient satisfaction. Several dimensions of nursing care quality, including reliability, responsiveness, assurance, empathy, and communication, were identified as major determinants of patient satisfaction. Most studies reported statistically significant relationships between nursing care quality and patient satisfaction with p-values less than 0.05. Conclusion: Nursing service quality plays a crucial role in improving patient satisfaction in hospital settings. Strengthening nursing care quality through improved communication, responsiveness, and professional competence can enhance patient experiences and overall health care service quality.